Synthesis and characterizations of novel magnetic and plasmonic nanoparticles - Dahal, Naween (Kansas State University, 2010)
This dissertation reports the colloidal synthesis of iron silicide, hafnium oxide core-gold shell and water soluble iron-gold alloy for the first time. As the first part of the experimentation, plasmonic and superparamagnetic nanoparticles of gold and iron are synthesized in the form of core-shell and alloy. The purpose of making these nanoparticles is that the core-shell and alloy nanoparticles exhibit enhanced properties and new functionality due to close proximity of two functionally different components. The synthesis of core-shell and alloy nanoparticles is of special interest for possible application towards magnetic hyperthermia, catalysis and drug delivery. The iron-gold core-shell nanoparticles prepared in the reverse micelles reflux in high boiling point solvent (diphenyl ether) in presence of oleic acid and oleyl amine results in the formation of monodisperse core-shell nanoparticles. The second part of the experimentation includes the preparation of water soluble iron-gold alloy nanoparticles. The alloy nanoparticles are prepared for the first time at relatively low temperature (110 oC). The use of hydrophilic ligand 3-mercapto-1-propane sulphonic acid ensures the aqueous solubility of the alloy nanoparticles. Next, hafnium oxide core-gold shell nanoparticles are prepared for the first time using high temperature reduction method. These nanoparticles are potentially important as a high κ material in semiconductor industry. Fourth, a new type of material called iron silicide is prepared in solution phase. The material has been prepared before but not in a colloidal solution. The Fe3Si obtained is superparamagnetic. Another phase β-FeSi2 is a low band gap (0.85 eV) semiconductor and is sustainable and environmentally friendly. At last, the iron monosilicide (FeSi) and β-FeSi2 are also prepared by heating iron-gold core-shell and alloy nanoparticles on silicon (111) substrate. The nucleation of gaseous silicon precursor on the melted nanoparticles results the formation of nanodomains of FeSi and β-FeSi2. A practical application of these nanoparticles is an important next step of this research. Further improvement in the synthesis of β-FeSi2 nanoparticles by colloidal synthetic approach and its application in solar cell is a future goal.
Keywords: Magnetic nanoparticles; Plasmonic nanoparticles; Colloidal synthesis; Silicide; Iron gold; Alloy; Chemistry, General (0485); Chemistry, Inorganic (0488); Engineering, Materials Science (0794)